2018
DOI: 10.1016/j.ebiom.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Potential Diagnostic Power of Blood Circular RNA Expression in Active Pulmonary Tuberculosis

Abstract: BackgroundCircular RNAs (circRNAs) are a class of novel RNAs with important biological functions, and aberrant expression of circRNAs has been implicated in human diseases. However, the feasibility of using blood circRNAs as disease biomarkers is largely unknown.MethodsWe explored the potential of using human peripheral blood mononuclear cell (PBMC) circRNAs as marker molecules to diagnose active pulmonary tuberculosis (TB).FindingsFirst, we demonstrated that circRNAs are widely expressed in human PBMCs and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
54
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 66 publications
4
54
1
1
Order By: Relevance
“…, testes (Liang et al 2017b), peripheral whole blood 62 (Memczak et al 2015), peripheral blood mononucleotide cells (Qian et al 2018), platelets 63 (Alhasan et al 2016), and exosomes (Li et al 2015a). CircRNAs have also been related to the 64 development of the fetal human brain (Szabo et al 2015), mouse brain (You et al 2015), fetal 65 porcine brain (Veno et al 2015), and Drosophila neural systems (Westholm et al 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…, testes (Liang et al 2017b), peripheral whole blood 62 (Memczak et al 2015), peripheral blood mononucleotide cells (Qian et al 2018), platelets 63 (Alhasan et al 2016), and exosomes (Li et al 2015a). CircRNAs have also been related to the 64 development of the fetal human brain (Szabo et al 2015), mouse brain (You et al 2015), fetal 65 porcine brain (Veno et al 2015), and Drosophila neural systems (Westholm et al 2014).…”
mentioning
confidence: 99%
“…In addition, aberrant circRNA expression is related to 68 human diseases , including human cancers (Meng et al 2017), neural 69 degenerative diseases (Kumar et al 2017), hematological malignancies (Bonizzato et al 2016), 70 and infectious diseases (Qian et al 2018). However, these conclusions might be preliminary and premature, since the circRNA profiles 82 examined in these studies were derived from relatively small datasets, such as RNA sequencing 83…”
mentioning
confidence: 99%
“…Of them, 145 circRNAs were elevated while only 26 circRNAs were reduced in TB samples compared with the controls, which were in line with the report that the circRNA's magnitude in PBMCs from active TB patients was significantly increased. 15 Moreover, our results showed that the expression pattern of circRNAs in PBMCs is similar to that in plasma, 16 where the most dysregulated circRNAs were enhanced upon Mtb infection. This indicates that circRNAs are possibly turned on to promote the pathogenesis and progression of To further address the feasibility of these verified circRNAs as potential biomarkers for active TB diagnosis, ROC curve was applied to evaluate their diagnostic value.…”
Section: Discussionmentioning
confidence: 56%
“…However, the three dysregulated circRNAs were not observed in the previous findings mentioned above. 13,15,21 This F I G U R E 4 Detailed presentation of interactions between hsa_circRNA_101128 and its five potential miRNA targets. The 2D structure displayed the MRE sequence, pairing of miRNA target nucleotides and seed type.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs are reproducibly and easily detected in clinical blood samples. Stable and enriched circRNAs have been found in peripheral blood [19,20], as well as blood components, such as exosomes [21], plasma [22], platelets [23], erythrocytes [24], and mononuclear cells [25].…”
Section: Discussionmentioning
confidence: 99%